PENINGKATAN KEMAMPUAN MENGENAL BENDA-BENDA SEKITARNYA MENGGUNAKAN ALAT PERAGA LOTTO WARNA PADA KELOMPOK B TK NEGERI 1 AIR MERAH TAHUN PELAJARAN 2021/2022 - Desi Murniati Siregar (JURNAL TEMATIK, 2022)
This research was conducted on children in Group B of TK Negeri 1 Air Merah for the academic year 2021/2022. According to the results of observations that the learning scores of children in Group B in recognizing the objects around them are very low. The purpose of this study is to describe learning outcomes using Color Lotto teaching aids. The method used is a descriptive method with the type of Classroom Action Research (CAR), each cycle begins with planning, observation, action, and reflection. The results showed that in Cycle I there were 2 meetings. Meeting 1 consisting of 11 children, the number of children who have not developed there are 2 children (18%), children who are starting to develop are 8 children (73%), children who are developing according to expectations are 1 child (9%) and are still developing very well. there isn't any yet. Meanwhile, at meeting 2, there were 7 children (64%), 4 children (36) who had not developed yet, and 4 children (36) who had developed very well. Learning outcomes in Cycle II there are 2 meetings. Meeting 1 consisting of 11 children, the number of children who have not developed yet, children who are starting to develop there are 3 children (27%), children who are developing as expected there are 6 children (55%) and very well developed as much as 2 (18%) . While at the second meeting the number of children who had not developed was not there, there were 2 children who began to develop (18%), 6 children who developed as expected (55%) and 3 children who developed very well (27%). Thus, it can be concluded that using a color lotto can improve learning outcomes in the material about recognizing the color of surrounding objects in TK Negeri 1 Air Merah.